2003
DOI: 10.1103/physrevb.67.174424
|View full text |Cite
|
Sign up to set email alerts
|

Interface and bulk properties of Fe/Mn sandwich structures

Abstract: Structural and magnetic properties of Fe(5 nm)/Mn(t Mn )/Fe(5 nm) (t Mn from 0.5 to 3.0 nm͒ sandwich structures, grown by molecular-beam epitaxy between 50°C and 150°C, were investigated using reflection high-energy electron diffraction ͑RHEED͒, x-ray-diffraction, Mössbauer spectroscopy, and magnetization measurements. Epitaxial bct-Mn structures only form for t Mn Ͻ1 nm, independently of the growth temperature. Room-temperature conversion electron Mössbauer spectra are composed of two magnetic components with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
(27 reference statements)
1
11
0
1
Order By: Relevance
“…Passamani et al [32] have applied a thermodynamic model based on the different melting points of the deposited materials to explain the larger atomic interdiffusion at the upper Mn/Fe interface in Fe/Mn/Fe trilayers deposited by MBE. If we apply this model to our results, it is easy to explain why the atomic diffusion at the top NiFe/FeMn interface is stronger than that obtained for the bottom.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Passamani et al [32] have applied a thermodynamic model based on the different melting points of the deposited materials to explain the larger atomic interdiffusion at the upper Mn/Fe interface in Fe/Mn/Fe trilayers deposited by MBE. If we apply this model to our results, it is easy to explain why the atomic diffusion at the top NiFe/FeMn interface is stronger than that obtained for the bottom.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Within these heterostructures, previous works on Ferromagnetic(F)/Mn-based systems have shown that finite size effects, hybridization mechanism and interfacial mixing could lead to very diverse type of magnetic behavior. Some authors have determined a F arrangement of the Mn based layer [7][8][9], whereas an antiferromagnet(AF) arrangement was revealed by others [10][11][12][13][14][15]. It could also be noted that even F x Mn 1À x bulk materials exhibit competing interactions with stoichiometric regions of F and AF order, enclosing intermediate stoichiometric region in which only short range order occurs [16].…”
Section: Introductionmentioning
confidence: 92%
“…It should be noted that Fe x Mn 1À x (Co x Mn 1À x ) was determined as antiferromagnetic at room temperature if x is smaller than 0.8 [17][18][19][20][21] (0.68 [22]). The assumption that interdiffusion is taking place at the interface is also supported by previous experimental study on annealed Fe/Mn [13] and by thermodynamic consideration involving binding energies between Fe and Mn [7]. Considering a dead interfacial layer, the M s dependence with t F can be described as [23]:…”
Section: Introductionmentioning
confidence: 93%
“…Different models, either thermodynamic [11] or ballistic [9], have been proposed to explain the asymmetry of the interfaces. These models do not account for the cause of this chemical asymmetry, which in our case could originate from the difference between Fe and Mn surface energies, 2.939 J m À 2 and 1.440 J m À 2 , respectively [12,13].…”
Section: Chemical Depth Profilesmentioning
confidence: 99%